Informed consent: Issues and challenges - Nijhawan, Lokesh; Janodia, Manthan; Muddukrishna, B; Bhat, K; Bairy, K; Udupa, N; Musmade, Prashant (Journal of advanced pharmaceutical technology and research, 2013)
Informed consent is an ethical and legal requirement for research involving human participants. It is the process where a participant is informed about all aspects of the trial, which are important for the participant to make a decision and after studying all aspects of the trial the participant voluntarily confirms his or her willingness to participate in a particular clinical trial and significance of the research for advancement of medical knowledge and social welfare. The concept of informed consent is embedded in the principles of Nuremberg Code, The Declaration of Helsinki and The Belmont Report. Informed consent is an inevitable requirement prior to every research involving human being as subjects for study. Obtaining consent involves informing the subject about his or her rights, the purpose of the study, procedures to be undertaken, potential risks and benefits of participation, expected duration of study, extent of confidentiality of personal identification and demographic data, so that the participation of subjects in the study is entirely voluntary. This article provides an overview of issues in informed consent: The obligations of investigator, sponsor and Institutional Review Board to protect rights and welfare of human research subjects. It discusses about the basic elements of informed consent and the process to be followed while obtaining informed consent. Some of the circumstances under which informed consent can be waived and ethical challenges faced by physicians in obtaining informed consent from subjects are also highlighted in this article.